1968
DOI: 10.1001/jama.205.3.134
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas exotoxin shock. A preliminary report of studies in dogs

Abstract: A study of shock following infusion of a newly described exotoxin from Pseudomonas aeruginosa (strain P-A-103)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

1973
1973
1998
1998

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 10 publications
1
15
0
Order By: Relevance
“…This observation agrees with pre vious findings [4], It is also clear that the changes observed in the behav iour of the platelets and fibrinogen is induced by the exotoxin injection. Previous experiences [6,19] reveal that the untraumatized dog receiving saline infusion shows no changes of blood or organ concentration of la belled platelets or fibrinogen.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This observation agrees with pre vious findings [4], It is also clear that the changes observed in the behav iour of the platelets and fibrinogen is induced by the exotoxin injection. Previous experiences [6,19] reveal that the untraumatized dog receiving saline infusion shows no changes of blood or organ concentration of la belled platelets or fibrinogen.…”
Section: Discussionsupporting
confidence: 92%
“…It is known that the liver is the target organ in canine shock states; Atik et al [4] for example, have shown an increased portal pressure during this type of experiment. How ever, the significance of the platelet accumulation in organ is unclear.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…P. aeruginosa is known to produce many potent toxins (2,3,6,8,(22)(23)(24)(25)(26)(27)(28)(29)33), and one is claimed to be responsible for death in experimental Pseudomonas infections (25 with 0.2 ml of tobramycin (50 mg/ml from Eli Lilly), 0.9 ml of bacterial suspension with 0.1 ml of 10% Formalin, 0.9 ml of bacterial suspension with 0.1 ml of 1 M HCl, and 0.9 ml of bacterial suspension with 1.0 ml of 95% ethyl alcohol. The four suspensions were then placed in a water bath at 37 C for 60 min.…”
mentioning
confidence: 99%
“…sion due to a decrease in peripheral resistance (7,8). However, the pathophysiologic mechanism of this decrease in peripheral vascular resistance is not absolutely clear.…”
Section: Introductionmentioning
confidence: 99%